Commentary upon ‘should collective bargaining and labor relations be less adversarial?’ - Koehn, Donald R. (Journal of business ethics, 1985)
My commentary calls attention to what makes Mr. Bowie's paper well worth intensive consideration. In my brief evaluation, however, I only lay out three incoherent elements of his proposed family model of labor-management relations., I argue that complete job security is not compatible with complete freedom to change firms; that, in practice, such security for all employees is not compatible with the shifting demand of our economic system, and that the model includes two kinds of spouse relationships — one affectional and another competitive — that are incoherent with one another. My point is not that Mr. Bowie's model is fatally flawed, but that it needs to be improved.